2017
DOI: 10.3233/adr-170011
|View full text |Cite
|
Sign up to set email alerts
|

Survival Curves and Behavioral Profiles of Female 3xTg-AD Mice Surviving to 18-Months of Age as Compared to Mice with Normal Aging

Abstract: New evidence reveals a high degree of heterogeneity in Alzheimer’s disease (AD) clinical and temporal patterns, supporting the existence of several subgroups of patients. Prognosticators of end-of-life dementia specific to elderly patients are necessary to address this heterogeneity. Among 3xTg-AD mice, a widely-used model for AD, a very small number of animals overcome advanced neuropathological stages of disease beyond 18 months of age. They are usually females, which reach longevity in spite of worse neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 34 publications
(37 reference statements)
9
32
2
Order By: Relevance
“…The crosstalk refers to the oxi-inflamaging theory developed in PAM and NPAM mice where the divergence of the speed of the aging process (premature in PAM and normal in NPAM) was correlated with immune function, oxidative stress, and worse/better copying with stress strategies in the TM (Guayerbas et al, 2001). While neophobia and worse long-term memory were found to be correlated with reduced survival in female NTg and 3xTg-AD mice (Torres-Lista et al, 2017), it was surprising that memory variables did not correlate with survival in the present work, probably due to the mortality bias, as discussed above. Thus, this was probably because the impairment was less pronounced in the current male sample, as correlation was only found with the level of optimization of the performance (day 4) in the water maze.…”
Section: Discussioncontrasting
confidence: 43%
“…The crosstalk refers to the oxi-inflamaging theory developed in PAM and NPAM mice where the divergence of the speed of the aging process (premature in PAM and normal in NPAM) was correlated with immune function, oxidative stress, and worse/better copying with stress strategies in the TM (Guayerbas et al, 2001). While neophobia and worse long-term memory were found to be correlated with reduced survival in female NTg and 3xTg-AD mice (Torres-Lista et al, 2017), it was surprising that memory variables did not correlate with survival in the present work, probably due to the mortality bias, as discussed above. Thus, this was probably because the impairment was less pronounced in the current male sample, as correlation was only found with the level of optimization of the performance (day 4) in the water maze.…”
Section: Discussioncontrasting
confidence: 43%
“…The behavioral effects were assessed at advanced stages (13 month of age) when both amyloid and tau pathologies are present ( Oddo et al, 2003 ). At this age, we have consistently reported that survival male 3xTg-AD mice starts to be compromised ( Giménez-Llort et al, 2008 , 2010 ; García-Mesa et al, 2016 ; Torres-Lista et al, 2017 ). Effects were compared to age-matched NTg mice with normal aging, that according to the background strain represent overcoming the middle age.…”
Section: Discussionmentioning
confidence: 88%
“…In this other test, which did not reach statistical significance, the subsequent analysis of the long-term habituation in the activity cages showed a worse (lower) pattern in the 3xTg-AD mice. Our laboratory has previously described the convergence of profiles in the context of poor aging and related physical and cognitive declines in NTg mice as part of the complexity of age-related scenarios and heterogeneity among all populations, including wild-type mice (not just 3xTg-AD mice) ( 69 ). Interestingly, these smooth patterns in middle-aged mice housed in standard conditions also emphasized the impact of isolation shown as prominent levels of both horizontal and vertical activities.…”
Section: Discussionmentioning
confidence: 99%